Avian Influenza A Virus in Wild Birds in Highly Urbanized Areas - Verhagen, Josanne H.; Munster, Vincent J.; Majoor, Frank; Lexmond, Pascal; Vuong, Oanh; Stumpel, Job B. G.; Rimmelzwaan, Guus F.; Osterhaus, Albert D. M. E.; Schutten, Martin; Slaterus, Roy; Fouchier, Ron A. M. (PLOS ONE, 2012)
Avian influenza virus (AIV) surveillance studies in wild birds are usually conducted in rural areas and nature reserves. Less is known of avian influenza virus prevalence in wild birds located in densely populated urban areas, while these birds are more likely to be in close contact with humans. Influenza virus prevalence was investigated in 6059 wild birds sampled in cities in the Netherlands between 2006 and 2009, and compared with parallel AIV surveillance data from low urbanized areas in the Netherlands. Viral prevalence varied with the level of urbanization, with highest prevalence in low urbanized areas. Within cities virus was detected in 0.5% of birds, while seroprevalence exceeded 50%. Ring recoveries of urban wild birds sampled for virus detection demonstrated that most birds were sighted within the same city, while few were sighted in other cities or migrated up to 2659 km away from the sample location in the Netherlands. Here we show that urban birds were infected with AIVs and that urban birds were not separated completely from populations of long-distance migrants. The latter suggests that wild birds in cities may play a role in the introduction of AIVs into cities. Thus, urban bird populations should not be excluded as a human-animal interface for influenza viruses.